Education And Employability With Special Reference To Rural Assam - Kongkee Devi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Education can be considered as a back bone of socio-economic development of a country. Today, the developed countries have hundred percent of literacy rate that helps them in occupying the better position in world economy. Strength of education helps an individual as well as a country in progressing in every aspect of development. According to census 2011, India has 74.04% literacy rate which creates a lot of difficulties in various aspects of development of the country. Moreover, it is in vague that the children who are fortunate to pursue education are getting quality education or not. Because, sometimes quality may compromise in order to fulfilling the growing demands of education. The people who are equipped with quality education are getting a lot of opportunities to find a better place in job market. As a result, now a day a major social issue is emerged namely unemployment which restrains the economic, social, political and other developmental aspects of a country. According to the NSSO Reports, 2011-12, unemployment rate in rural and urban areas on Usual Status basis are 4.5% and 5.6% of the total population respectively. Employability is comprises of set of skills that makes one capable of getting a job and maintain it. In this competitive era, pursuing skill development courses are very important rather than gathering knowledge on core subjects which is not related and suitable for getting established. Therefore, it is very important to provide vocational education for generating more skillful and competent manpower. Govt. of Assam as well as India has taken various initiatives for developing skill and competency of every individual in order to effectively tackle the unemployment problem. This paper is intended to study the rural employment and unemployment in relation to the education in Assam and also suggest some remedial measures for effectively deal with the unemployment problem..